Cerebro arteriovenous malformation presenting as recurrent epistaxis: a rare entity - Dr.D. Manoj; Dr.Venkatasuryanarayana; Dr. C.R. Banapurmath (Pediatric Review: International Journal of Pediatric Research, 2018)
An arteriovenous malformation is an abnormal tangle of blood vessels in the brain or spine. Some AVM’s have no specific symptoms and little or no signs to one’s life or health, while others cause severe and devastating effects when they bleed. Treatment options range from conservative watching to aggressive surgery, depending on the type, symptoms and location of the AVM.